1998
DOI: 10.23986/afsci.5605
|View full text |Cite
|
Sign up to set email alerts
|

Concentrate feeding and milk yield based on the field data of milk recorded herds

Abstract: Field data from 16 051 Finnish milk recorded herds including milk yield (MY), feed consumption, feed analyses, and the herd effect for milk yield (HMILK) obtained from the national breeding value estimation program, were analysed to detect the influence of concentrate feeding on milk production. HMILKs are deviations from the average national level with mean of 45 kg and SD of 722 kg. Mean MY was 6917 kg and mean dry matter intake (DMI) 5679 kg per cow per year. The effect of concentrate feeding on HMILK and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…Diet OG-L cows produced more milk than Diet OG-E animals due to higher DM intake and higher concentrate intake. Higher DM intake and greater consumption of concentrates has been associated with higher milk production among cows fed orchardgrass rations (Weiss and Shockey, 1991;Huhtanen, 1993;Kaustello et al, 1998). Cows offered Diet OG-L had higher milk protein and milk urea nitrogen levels and produced more milk protein per day ( Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…Diet OG-L cows produced more milk than Diet OG-E animals due to higher DM intake and higher concentrate intake. Higher DM intake and greater consumption of concentrates has been associated with higher milk production among cows fed orchardgrass rations (Weiss and Shockey, 1991;Huhtanen, 1993;Kaustello et al, 1998). Cows offered Diet OG-L had higher milk protein and milk urea nitrogen levels and produced more milk protein per day ( Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the genetic trend of dairy cows for milk protein concentration is close to zero (FABA, 2005) suggesting that the positive phenotypic trend is due to more intensive feeding or more evidently because farms with a low feeding intensity have finished milk production (Kaustell et al, 1996;Huhtanen and Nousiainen, 2004). Kaustell et al (1998) reported based on milk recording data that with increasing milk yield the increase in milk protein only partly compensates the lowering milk fat concentration. Consequently raw milk DM concentration tends to decrease along with more intensive feeding and increasing milk yield.…”
Section: Milk Fat and Protein Concentrationmentioning
confidence: 99%
“…Consequently, relatively large differences in the protein content of dairy cow rations can exist between individual countries. Finnish dairy cow rations typically contain lower amounts of protein (150 g CP/kg DM; Kaustell et al 1998) than diets fed in other European countries, such as Holland (185-220 g/kg DM, Tamminga 1992) or the United Kingdom (180-190 g/kg DM, N.W. Offer, personal communication).…”
Section: Protein Feeding In Finlandmentioning
confidence: 99%
“…Reproductive studies in Finnish cows have tended to concentrate on the role of energy intake (Miettinen 1990a, 1991), feeding regimen (Heinonen et al 1988, Miettinen 1990c breed (Kuni and Pirinen, 1988) or parity (Miettinen 1990b) on reproductive efficiency. In Finland, dairy cow rations contain only relatively moderate CP concentrations, typically 150 g/kg DM (Kaustell et al 1998) suggesting that potential reproductive inefficiencies due to excessive protein feeding are likely to be minimised. Furthermore, Miettinen (1991) reported that the proportion of cows fed diets according to Finnish feeding standards with plasma urea concentrations lower than 150 mg/l at 14 and 60 d postpartum was 0.89 and 0.65, respectively.…”
Section: Associations Between Protein Feeding and Reproductive Efficimentioning
confidence: 99%
See 1 more Smart Citation